Serodiagnosis of hydatidosis in sheep and goats in Siirt province, Türkiye, and an alternative approach to the interpretation of serology results - Celik, Burcak Aslan; Selcuk, Muhammed Ahmed; Celik, Figen; Celik, Ozgur Yasar; Uslug, Muhammet; Tekin, Afra Sena; Simsek, Sami (Elsevier, 2025)
Cystic echinococcosis (CE) is one of the most important zoonotic diseases worldwide, affecting both humans and animals, caused by Echinococcus granulosus sensu lato. The diagnosis of CE is based on the evaluation of imaging, serological, molecular and clinical findings. The aim of this study was to develop a diagnostic method that can be used for herd-based diagnosis of CE, which is commonly observed in sheep and goats, and to prevent economic losses by treating positive animals. Antigen B rich partially purified cyst fluid antigen was prepared from a sheep liver hydatid cyst. To determine the sensitivity and specificity of the antigen B-rich partially purified cyst fluid antigen, a Western blot test was first performed using hydatid cyst positive sera from 24 sheep and 20 goats collected from the abattoir and sera from 27 newborn lambs and 23 goat kids as negative controls. Subsequently, 500 sera were collected from 250 sheep and 250 goats from Siirt province and its districts. The strongest band was at 72 kDa, followed by bands at 55 kDa and 28 kDa in SDS-PAGE. According to the 43 kDa band as reference the sensitivity was 62.5 %. and specificity was 96.2 % in sheep. Besides, of the 250 sheep sera collected from the field, and the seroprevalence was 52.80 %. In goats, the sensitivity of WB was 55 % and the specificity was 86.9 %. On the other hand, the seroprevalence was 44.4 % in goats. In conclusion, the production of antigens that are easy to prepare, inexpensive and can be used in field screening for CE will be important in terms of treating positive sheep (even when CE and other helminth parasites are present together) with albendazole and preventing economic losses.
Keywords: Hydatid cyst; Sheep; Goat; Seroprevalence; Western blot; T & uuml;rkiye